Chronic health conditions reported by male inmates newly admitted to Canadian federal penitentiaries - Stewart, Lynn A. (CMAJ Open, 2015)
BACKGROUND: International health studies have shown that inmates have higher rates of infectious diseases, chronic diseases and psychiatric disorders relative to the general population. We conducted a systematic collection of data on chronic physical health conditions reported by newly admitted inmates in Canadian federal penitentiaries. METHODS: Over a 6-month period from April to September 2012, we collected and analyzed data from a standardized health interview routinely conducted with consenting incoming male inmates (n = 2273). Prevalence rates of health conditions were determined and disaggregated by age (< 50 yr and ≥ 50 yr) and by Aboriginal status. RESULTS: The most common health conditions reported by respondents were head injury (34.1%), back pain (19.3%), asthma (14.7%) and hepatitis C virus (HCV) infection (9.4%). Rates of many health conditions were higher among inmates 50 years of age or older than among younger inmates. Compared with their non-Aboriginal counterparts, Aboriginal inmates had higher rates of head injury and HCV infection. INTERPRETATION: Our study provides a benchmark that can be used to examine health trends within Canada’s federal penitentiaries over time and points to subgroups of newly admitted inmates for whom health services may need to be concentrated.